Effect of including carob pulp in the diet of fattening pigs on the fatty acid composition and oxidative stability of pork. (February 2015) - Inserra, L.; Luciano, G.; Bella, M.; Scerra, M.; Cilione, C.; Basile, P.; Lanza, M.; Priolo, A.
Abstract: The effect of feeding pigs with carob pulp on meat quality was investigated. Nine pigs were finished on a conventional concentrate-based diet (control), while two groups received a diet comprising of the same ingredients with the inclusion of 8% or 15% carob pulp (Carob 8% and Carob 15%, respectively). Feeding carob-containing diets reduced the concentration of saturated fatty acids in the muscle, increased the concentration of monounsaturated fatty acids in meat ( P < 0.01) and of n-3 polyunsaturated fatty acids (PUFAs) and reduced the n-6/n-3 PUFA ratio ( P < 0.001). The meat underwent slow oxidative deterioration over 9 days of storage. However, the Carob 15% treatment increased meat susceptibility to lipid oxidation across storage ( P = 0.03), while the dietary treatment did not affect meat colour stability. In conclusion, feeding pigs with carob pulp could represent a strategy, in the Mediterranean areas, to naturally improve meat nutritional value and to promote the exploitation of this local feed resource. Highlights: Diets containing carob induced modifications of the intramuscular fatty acids. Diets containing carob reduced the concentration of saturated fatty acids in the muscle. Diets containing carob increased the n-3 polyunsaturated fatty acids in the muscle. Diets containing carob did not affect meat colour stability. A diet including 15% carob slightly increased lipid oxidation over aerobic storage.